KEDUDUKAN PEGAWAI NOTARIS SEBAGAI SAKSI DALAM AKTA AUTENTIK PADA PROSES PENYIDIKAN DAN PERADILAN DITINJAU UNDANG-UNDANG JABATAN NOTARIS - Andony, Fakta; Afriana, Anita; Prayitno, Indra (ADHAPER: Jurnal Hukum Acara Perdata, 2020)
The existence of a Deed Witness is part of the formal aspect of the deed. Without a witness deed, t the notary deed as a Notary Deed, but only has the power of proof as an underhand deed. In addition, the actions of Notary employees as witnesses to deeds in each Notaryâ€™s deed are included in the notary fi eld, so that if it is linked to Article 16 paragraph (1) letter f of the Notary Position Law regarding keeping everything concerning deeds made by Notaries, the employees should a notary as a witness to the deed must be able to keep the contents of the deed confi dential. ThisÂ article intends to fi nd out about the process of summoning notary employees who are witnesses to the deed for investigation and trial in connection with the confi dentiality of the contents of the deed and protecting the confi dentiality of the contents of the deed in the investigation and judicial process involving notary offi ce employees as witnesses to the deed. The results show that summoning notary employees who are deed witnesses for investigation and trial based on UUJN is that there are no rules for special procedures for calling witnesses to deeds in the investigation and trial process. A witness to deed does not have the right of refusal as a notary, therefore what applies is the provision as reference to KUHAP and HIR/Rbg. Protection of the confi dentiality of the contents of the deed in the investigation and judicial process involving notary offi ce employees as witnesses to the deed that there is no obligation for notary employees who are witnesses to the deed to keep the contents of the deed secret during the investigation and trial process. Notary employees who are witnesses to the deed do not completely violate the law because there are no rules in UUJN that regulate the oath to keep the contents of the deed confi dential